2020
DOI: 10.1080/15476286.2020.1712544
|View full text |Cite
|
Sign up to set email alerts
|

TRMT2B is responsible for both tRNA and rRNA m5U-methylation in human mitochondria

Abstract: RNA species play host to a plethora of post-transcriptional modifications which together make up the epitranscriptome. 5-methyluridine (m 5 U) is one of the most common modifications made to cellular RNA, where it is found almost ubiquitously in bacterial and eukaryotic cytosolic tRNAs at position 54. Here, we demonstrate that m 5 U54 in human mitochondrial tRNAs is catalysed by the nuclear-encoded enzyme TRMT2B, and that its repertoire of substrates is expanded to ribosomal RNAs, catalysing m 5 U429 in 12S rR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 55 publications
2
41
0
1
Order By: Relevance
“…Sequence homology analysis identified two mammalian proteins, TRMT2A and TRMT2B, as m 5 U methyltransferase candidates (Carter et al, 2019). TRMT2A was identified as the enzyme responsible for m 5 U54 in the cytosol (Carter et al, 2019;Powell and Minczuk, 2020), while TRMT2B was suggested to methylate tRNAs in mitochondria (de Crécy-Lagard et al, 2019). 2 A937 (Cotney and Shadel, 2006;Liu et al, 2019) KsgA/RsmA m 6 2 A1518 m 6 2 A1519 16S rRNA (Helser et al, 1972;Poldermans et al, 1979;Formenoy et al, 1994) (Droogmans et al, 2003) A recent study by Laptev et al showed that Trmt2b knock-out in mouse cells leads to a lack of m 5 U425 methylation (mouse numbering, equivalent to human m 5 U429, mtDNA position: m.1076T) in mt-12S rRNA as well as of U54 in certain mitochondrial tRNAs, indicating that TRMT2B might act as a dual tRNA/rRNA methyltransferase (Laptev et al, 2019).…”
Section: Trmt2b (M5u429)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence homology analysis identified two mammalian proteins, TRMT2A and TRMT2B, as m 5 U methyltransferase candidates (Carter et al, 2019). TRMT2A was identified as the enzyme responsible for m 5 U54 in the cytosol (Carter et al, 2019;Powell and Minczuk, 2020), while TRMT2B was suggested to methylate tRNAs in mitochondria (de Crécy-Lagard et al, 2019). 2 A937 (Cotney and Shadel, 2006;Liu et al, 2019) KsgA/RsmA m 6 2 A1518 m 6 2 A1519 16S rRNA (Helser et al, 1972;Poldermans et al, 1979;Formenoy et al, 1994) (Droogmans et al, 2003) A recent study by Laptev et al showed that Trmt2b knock-out in mouse cells leads to a lack of m 5 U425 methylation (mouse numbering, equivalent to human m 5 U429, mtDNA position: m.1076T) in mt-12S rRNA as well as of U54 in certain mitochondrial tRNAs, indicating that TRMT2B might act as a dual tRNA/rRNA methyltransferase (Laptev et al, 2019).…”
Section: Trmt2b (M5u429)mentioning
confidence: 99%
“…2 A937 (Cotney and Shadel, 2006;Liu et al, 2019) KsgA/RsmA m 6 2 A1518 m 6 2 A1519 16S rRNA (Helser et al, 1972;Poldermans et al, 1979;Formenoy et al, 1994) (Droogmans et al, 2003) A recent study by Laptev et al showed that Trmt2b knock-out in mouse cells leads to a lack of m 5 U425 methylation (mouse numbering, equivalent to human m 5 U429, mtDNA position: m.1076T) in mt-12S rRNA as well as of U54 in certain mitochondrial tRNAs, indicating that TRMT2B might act as a dual tRNA/rRNA methyltransferase (Laptev et al, 2019). At the same time, Powell and Minczuk showed that TRMT2B is located in human mitochondria and plays an essential role in methylation of both tRNAs and 12S rRNA (Powell and Minczuk, 2020). Similar to yeast Trm2 (Nordlund et al, 2000), no apparent impairment of mitochondrial tRNA stability, mitoribosome integrity, or mitochondrial protein synthesis was detected upon TRMT2B loss in human cells (Powell and Minczuk, 2020).…”
Section: Trmt2b (M5u429)mentioning
confidence: 99%
“…Modified 12S rRNA nucleotide m 5 U429 is unique for vertebrate mitochondria; equivalent nucleotides in other types of ribosomes are not modified. It was recently demonstrated that U429 is methylated by protein TRMT2B [ 9 , 11 ], a dual specificity enzyme which is also capable to form m 5 U54 residue in the T-loop of a number of mitochondrial tRNAs. Although equivalent nucleotides in other ribosomes are not modified, bacteria and yeast have homologues tRNA-specific methyltransferases TrmA [ 130 ] and Trm2 [ 131 ].…”
Section: Rrna Nucleotides Methylated Exclusively In the Mitochondrmentioning
confidence: 99%
“…This evolutionary history is reminiscent to the emergence of the dual specificity methyltransferase TRMT61B. However, unlike TRMT61B gene inactivation, which is phenotypically silent, TRMT2B gene inactivation resulted in a moderate decrease in the activity of ETC complexes containing mitochondrially encoded subunits, while the efficiency of mitochondrial translation was apparently unaffected [ 9 , 11 ].…”
Section: Rrna Nucleotides Methylated Exclusively In the Mitochondrmentioning
confidence: 99%
See 1 more Smart Citation